Influences of data filtering on human–computer interaction by gaze-contingent display and eye-tracking applications - Veneri, Giacomo; Federighi, Pamela; Rosini, Francesca; Federico, Antonio; Rufa, Alessandra (Computers in human behavior, 2010)
We describe an interactive gaze-contingent display (GCD) applied to clinical applications; the system uses a simple texture hole to inhibit peripheral vision, to test and stress overt mechanisms of visual searching in normal subjects. The correct use of GCD in vision research is affected by tremor of the hole, due to system noise, nystagmus, eye blinking, calibration and subject reactivity. These issues compromise the execution of task. In order to obtain a stable GCD hole, we implemented a predictive gaze-contingent display (PGCD), fitting through dispersion of fixations and modulating a filter. The paper describes the PGCD and compare it with the common technique, providing evidence that humans fit exploration based on the characteristics of the computer system; in particular we found significant difference applying PGCD or a simple finite impulse response filter. We suggest that a correct human–computer interaction applied to neuropsychological context must be developed taking in consideration both technical point of view and human behavior.